A Dinuclear Molecular Iron(II) Silicate with Two High‐Spin Square‐Planar FeO4 Units1. Issue 19 (19th March 2013) - Pinkert, Denise; Demeshko, Serhiy; Schax, Fabian; Braun, Beatrice; Meyer, Franc; Limberg, Christian
<x xml:space="preserve">Abstract</x> Ferrous flatland: Two flattened FeIIO4 units that share an edge are found in the title compound (see structure). They are spanned by tripodal silanolate ligands, which form in situ from a trisilanol if iron ions are available for complexation. The compound approaches the situation in the natural iron silicate gillespite or in certain ceramics where square planar FeO4 units have also been found.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>